Perawatan Spiritual pada Pasien Kanker Payudara - Ni'mah Mufidah; Anggorowati Anggorowati; Suhartini Ismail (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to get an overview of Islamic spiritual interventions that can be applied to breast cancer patients. The research method used in this research is scoping review based on the Arksey and O'Malley way by searching articles through Databased: EBSCO, SpringerLink, Pubmed, ProQuest, Science Direct, and Scopus and using the keywords